2021
DOI: 10.3390/ma14226863
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Physiological Comfort Properties of Sportswear with Different Combination of Inner and Outer Layers

Abstract: Consumers expect high-performance functionality from sportswear. To meet athletic and leisure-time activity requirements, further research needs to be carried out. Sportswear layers and their specific thermal qualities, as well as the set and air layer between materials, are all important factors in sports clothing. This research aims to examine the thermal properties of sports fabrics, and how they are affected by structure parameters and maintained with different layers. Three inner and four outer layers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 39 publications
(47 reference statements)
0
12
0
Order By: Relevance
“…I cl estimation relying on lookup tables in ISO standards [8][9][10]12] and updated clothes databases [58,59] can be a fast solution for laboratory studies, but it is unfeasible to use such a scheme in real applications due to reasons: (i) looking up the I cl value for a person needs extra manual work which is tedious and expensive; (ii) if this look-up task is expected to be done automatically, the solution must have the ability to recognize hundreds of different garment combinations that vary in materials and number of layers as the latest research has revealed the significant importance of them in thermal comfort [2], which is far beyond the capability of existing algorithms.…”
Section: CL Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…I cl estimation relying on lookup tables in ISO standards [8][9][10]12] and updated clothes databases [58,59] can be a fast solution for laboratory studies, but it is unfeasible to use such a scheme in real applications due to reasons: (i) looking up the I cl value for a person needs extra manual work which is tedious and expensive; (ii) if this look-up task is expected to be done automatically, the solution must have the ability to recognize hundreds of different garment combinations that vary in materials and number of layers as the latest research has revealed the significant importance of them in thermal comfort [2], which is far beyond the capability of existing algorithms.…”
Section: CL Estimationmentioning
confidence: 99%
“…This kind of method takes advantage of different thermal properties (thermal resistance, thermal conductivity, thermal radiation, thermal convection, water evaporation, etc.) of different clothes in materials, thicknesses, and layers to maintain the body temperature in a comfortable range [2][3][4][5]. The other kind of method still focuses on the entire indoor environment but in a way that adjusts the microclimate according to each occupant's thermal need, which is the topic of this paper.…”
Section: Introductionmentioning
confidence: 99%
“…For example, textiles utilising fibre-based artificial muscles may react to sweating through contraction, thus exposing a larger skin area for improved cooling [6]. Combining different types of fabrics can also significantly affect the overall performance of clothing, allowing for clothes especially suited for a particular activity or climate [7]. Using modern technology, smart garments can also be designed to target very specific needs, such as treatment of physical disorders [8].…”
Section: State-of-the-artmentioning
confidence: 99%
“…The use of different material arrangements in sleeping bags has increased in recent years, allowing them to be used in a variety of conditions while maintaining comfort. The use of the most modern textile science and technology in the production of this type of materials is developing every day [ 12 , 13 , 14 ]. Winter sleeping bags must provide adequate thermal insulation, as well as protection against weather conditions, while summer sleeping bags must—oppositely—provide lower thermal insulation; therefore, different composition of raw materials should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies focused on the study of thermal properties in single and double-layer structures with variable raw material compositions to achieve the optimal level of comfort [ 12 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%